Material Cultures of Childhood in Second World War Britain - Moshenska, Gabriel (Material Culture and Modern Conflict, 2019)
Modern warfare is a unique cultural phenomenon. While many conflicts in history have produced dramatic shifts in human behaviour, the industrialized nature of modern war possesses a material and psychological intensity that embodies the extremes of our behaviours, from the total economic mobilization of a nation state to the unbearable pain of individual loss. Fundamentally, war is the transformation of matter through the agency of destruction, and the character of modern technological warfare is such that it simultaneously creates and destroys more than any previous kind of conflict.